Non-woven flax fibre reinforced acrylic based polyester composites: The effect of sodium silicate on mechanical, flammability and acoustic properties - M. F. Ahmad Rasyid; M. S. Salim; H. M. Akil; J. Karger-Kocsis; Z. A. Mohd. Ishak (eXPRESS Polymer Letters)
Non-woven flax fibre reinforced acrylic-based polyester (NFA) composites were prepared using an impregnation process. A mixture of acrylic-based polyester (Acrodur®) with varying sodium silicate (SS) loadings was applied to impregnate the non-woven flax fibre mat. Flexural tests were performed to evaluate the mechanical properties of the composites. Flammability properties were assessed via UL94 test and limiting oxygen index (LOI). The mechanical properties of NFA composites decreased substantially with increment in SS loading. The addition of SS resulted in significant improvement of flame retardancy, whereby UL94 rating enhanced from V-1 to V-0, while the LOI values increased from 24 to 40. Sound absorption coefficients of the NFA composites were measured via two-microphone transfer function technique in impedance tube. The sound absorption properties of NFA composites also improved with the incorporation of SS, whereby the sound absorption coefficient increased up to 0.87 at 2000 Hz frequency. Based on the overall evaluation, 20 wt% of SS effectively increased flame retardancy and sound absorption properties, along with moderate deterioration in flexural properties. The scanning electron microscopic (SEM) analysis of the composites surfaces displayed formation of voids and irregular structures at higher SS loading, which reduced the mechanical properties of NFA composites. The SEM images offered supportive evidences on the role of hollow lumen structures in natural fibres to ensure better sound absorption performance in NFA composites.